2021
DOI: 10.3390/ijms221810027
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Dichloroacetate Suppress Proliferation of Liver Cancer Cells by Inhibiting mTOR Complex 1

Abstract: The Warburg effect is important for cancer cell proliferation. This phenomenon can be flexible by interaction between glycolysis and mitochondrial oxidation for energy production. We aimed to investigate the anticancer effects of the pyruvate dehydrogenase kinase inhibitor, dichloroacetate (DCA) and the mitochondrial respiratory complex I inhibitor metformin in liver cancer cells. The anticancer effect of DCA and/or metformin on HepG2, PLC/PRF5 human liver cancer cell lines, MH-134 murine hepatoma cell lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…Synergism has been reported when DCA is combined with different drugs for anti-cancer research: DCA/cisplatin or gefitnib or elotinib ( Al-Azawi et al, 2021 ), DCA/metformin ( Kim et al, 2021 ; Klose et al, 2021 ; Korsakova et al, 2021 ), DCA/3-bromopyruvate ( Nikravesh et al, 2021 ), DCA/sorafenib ( Sun et al, 2021 ), DCA/PX-478 ( Parczyk et al, 2021 ) and DCA/erlotinib ( Dyrstad et al, 2021 ). Said synergistic effect has also been observed when Nic is combined with other agents: Nic/gemcitabine ( Guo et al, 2022b ), Nic/metformin ( Kang et al, 2021 ) and Nic/doxorubicin ( Lohiya and Katti, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synergism has been reported when DCA is combined with different drugs for anti-cancer research: DCA/cisplatin or gefitnib or elotinib ( Al-Azawi et al, 2021 ), DCA/metformin ( Kim et al, 2021 ; Klose et al, 2021 ; Korsakova et al, 2021 ), DCA/3-bromopyruvate ( Nikravesh et al, 2021 ), DCA/sorafenib ( Sun et al, 2021 ), DCA/PX-478 ( Parczyk et al, 2021 ) and DCA/erlotinib ( Dyrstad et al, 2021 ). Said synergistic effect has also been observed when Nic is combined with other agents: Nic/gemcitabine ( Guo et al, 2022b ), Nic/metformin ( Kang et al, 2021 ) and Nic/doxorubicin ( Lohiya and Katti, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…DCA has been shown to decrease serum pyruvate and lactate in a phase II clinical trial ( Lam et al, 2016 ). DCA decreases lactate level ( Michelakis et al, 2008 ), glucose consumption ( Kolesnik et al, 2020 ; Guo et al, 2022a ), lactate production ( Dyrstad et al, 2021 ; Kim et al, 2021 ) and lactate excretion ( Dyrstad et al, 2021 ), intracellular ATP ( Kim et al, 2021 ) and citrate ( El Sayed et al, 2019 ) but elevates succinate ( Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of mTOR is associated with lower tumor differentiation, worse prognosis, and early recurrence ( 22 ). Metformin can effectively inhibit HCC growth by inhibiting mTOR through the phosphatidylinositol-3-kinase (PI3K)/protein kinase B(AKT)/mTOR signal pathway ( 14 ). Metformin also has antitumor effects by reducing mitochondrial complex I in the respiratory chain to activate AMPK ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is vital to prevent recurrence after TACE in improving the long-term survival of patients. Metformin has recently attracted increasing attention due to its effects on inhibiting tumor cell proliferation and promoting tumor cell apoptosis ( 14 ). Some studies reported controversial data on its antitumor effects in non-surgical treatment ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…MET activates AMPK through STK11 (also experienced as LKB1), which has to do with multiple signaling pathways and affects cell growth, development, apoptosis, and other biological functions [ 13 , 23 , 24 ]. AMPK is the main regulator of cellular energy producing and the interaction between metabolism and tumors [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%